Japan's Official Development Assistance : Recent Issues and Future Directions - Kawai, Masahiro; Takagi, Shinji (World Bank, Washington, DC, 2014)
Japan remains the world's largest national donor of aid funds. But the Japanese government, facing prolonged economic stagnation and mounting public sector debt, is under increasing public pressure to reduce aid budgets and to use official development assistance in more explicit pursuit of Japan's own economic and political interests. Internationally, Japan continues to attract criticism for its emphasis on infrastructure projects and its limited willingness to participate in multilateral partnerships. The authors argue that Japan can meet these domestic and international challenges by developing a coherent national strategy for official development assistance, broadly designed to enhance effectiveness, accountability, and transparency.